Penerapan Model Kooperatif Number Head Together (NHT) untuk Meningkatkan Hasil Belajar IPS Siswa Kelas IV - Raini Raini (Indonesian Institute for Counseling, Education and Therapy (IICET), 2016)
Based on observation, it was known that learning achievement for Social subject of the fourth grade students at SDN 19 IV Koto Aur Malintang Kabupaten Padang Pariaman was not satisfied yet. It was assumed as the effect of ineffective learning model used in classroom. Cooperative learning model of NHT not only gives students the knowledge and understanding, but also educates them to socialize well in heterogenic groups. This research was aimed to improve students’ learningachievement of Social subject by implementing cooperative learning model of NHT. Data were obtained through observation and students’ test. Data were analyzed qualitatively and quantitatively. This research was held in two cycles. Researcher set the standard of students’ learning achievement as 75%. After cycle I, students’ learning achievement is 56,7%. After cycle II, students’ learning achievement is 80%. Based on the research result, it can be concluded that cooperative learning model of NHT can improve the learning achievement for Social subject of the fourth grade students at SDN 19 IV Koto Aur Malintang Kabupaten Padang Pariaman.